INKORPORASI MIKROEMULSI EKSTRAK ETANOL AKAR KELAKAI (Stenochlaena Palustris (Burn. F) Bedd.) PADA FORMULASI TONER WAJAH DENGAN VARIASI KONSENTRASI GLISERIN - Forestryana, Dyera; Muawiyyah, Walidatun; Indah Sayakti, Putri (Jurnal Insan Farmasi Indonesia, 2023)
The face is one part of the human body that needs to be kept healthy and clean. Efforts can be made to maintain facial cleanliness by using facial toner. The extract of kelakai root has activity as an antioxidant. Incorporation of kelakai root extract microemulsion in the toner formulation will increase the cleaning ability and optimal absorption of active substances. This research aims to obtain an optimum face toner formula. The kelakai roots were macerated with 70% ethanol solvent. The kelakai microemulsion consisted of Tween 80 35% w/v and PEG 400 15% w/v. Incorporation of 2% w/v microemulsion into the toner formula with varying glycerin concentrations of 2%, 3%, 4%, and 5% w/v. Evaluation through stability tests with organoleptic, homogeneity, pH, viscosity, clarity, and density. Organoleptic, homogeneity, and clarity before and after the stability test provide a liquid form, odorless, clear, and homogeneous color. In the pH test, the pH value of the preparation was stable in the pH range of 4.5-6.5. The viscosity of toner preparations is in a range of 1-24.5 cPs. The density stability with a range of 1.003-1.015 gr/mL. The optimum formula, namely F2 with 3% glycerin, provides good toner stability based on physical quality tests.